2002
DOI: 10.4049/jimmunol.169.2.1077
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Experimental Autoimmune Myasthenia Gravis in IL-6-Deficient Mice Is Associated with Reduced Germinal Center Formation and C3 Production

Abstract: To provide direct genetic evidence for a role of IL-6 in experimental autoimmune myasthenia gravis (EAMG), IL-6 gene KO (IL-6−/−) mice in the C57BL/6 background were immunized with Torpedo californica acetylcholine receptor (AChR) and evaluated for EAMG. Only 25% of AChR-immunized IL-6−/− mice developed clinical EAMG compared to 83% of C57BL/6 (wild-type) mice. A significant reduction in the secondary anti-AChR Ab of IgG, IgG2b, and IgG2c, but not the primary or secondary IgM response was observed in AChR-immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
86
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 46 publications
3
86
0
Order By: Relevance
“…Since this could be secondary to IL-6 deficiency, we measured autoantigen-induced Th17 responses in IL-6 -/-mice immunized with AChR/CFA. Consistent with previous reports [24], IL-6 -/-mice were resistant to the induction of EAMG. Importantly, IL-6 -/-mice had impaired capacity to mount AChR-induced production of IL-17 in CD4 + cells, while IFN-c production was not altered significantly (Fig.…”
Section: Il-6 -/-Mice Fail To Mount Achr-induced Th17 Responsessupporting
confidence: 93%
See 3 more Smart Citations
“…Since this could be secondary to IL-6 deficiency, we measured autoantigen-induced Th17 responses in IL-6 -/-mice immunized with AChR/CFA. Consistent with previous reports [24], IL-6 -/-mice were resistant to the induction of EAMG. Importantly, IL-6 -/-mice had impaired capacity to mount AChR-induced production of IL-17 in CD4 + cells, while IFN-c production was not altered significantly (Fig.…”
Section: Il-6 -/-Mice Fail To Mount Achr-induced Th17 Responsessupporting
confidence: 93%
“…In a previous study, IL-6 -/-mice were found resistant to the induction of EAMG [24]. Our current data taken in the content of recent findings [9] suggest that the resistance to EAMG could derive from faulty development of Th17 cells.…”
Section: Il-6 -/-Mice Fail To Mount Achr-induced Th17 Responsessupporting
confidence: 56%
See 2 more Smart Citations
“…However, only the two-component system was strongly dependent on the endogenous IL-6 activity in vivo (Figure 8). This was expected as the complement C3 upregulation in response to an immunogen was completely absent in the IL-6 À/À mice 41,42 and was probably regulated at the level of complement C3 promoter activation. 43,44 It is known that the TAT protein can transactivate inflammatory host genes, 45 including the IL-6 gene.…”
Section: Discussionmentioning
confidence: 79%